IMPROVEMENT OF AUDIT QUALITY CONTROL IN BANKS - Hamraqulov Elyor Oybek Ogli (Scholar Express Journals, 2023)
This article explores strategies to improve audit quality control in banks, emphasizing the importance of regulatory compliance, professional skepticism, and technology integration. The methods section outlines key approaches, including risk assessment, audit committee oversight, and peer review. Results showcase the positive impact of these strategies, leading to a robust discussion on the implications for the banking industry. The article concludes with actionable suggestions to enhance audit quality control and maintain trust in financial institutions.
Keywords: Audit quality control; banking industry; regulatory compliance; professional skepticism